Roles of the National Human Rights Commission in Managing Conflicts between Local People and the Cassava Starch Factory Draining Polluted Water into Klong Praprong - Phiewhorm, Sirilada; Jongkroy, Puntip (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2019)
The research objectives were to explore conflict issues between local people and the cassava starch factory that drained polluted water into Klong Praprong, to analyze the roles of the National Human Rights Commission, to compile problems and obstacles of the Commission in managing conflicts, and to formulate guidelines in alleviate operational problems and obstacle for the Commission. The research applied a qualitative method. Semi-structured interviews and document research were applied to collect data. To analyzed, content analysis was used. It was found that the conflict between local people and the factory that drained polluted water into Klong Praprong covered four issues; data conflicts being derived from the differences of the interpretation of data, interest conflicts from the irresponsibility of the factory, relationship conflicts being caused by the lack of trust of local people, and organization structure due to the bureaucrat’s long procedure. Among these problems, relationship problem was found most critical. Regarding the role of the National Human Rights Commission In resolving conflict, it was found that the Commission had play a supporting role as a mediator in receiving petitions from local people because the Department of Industrial Works that should play a leading role has failed to eliminate the conflicts in time. The research also illustrated that the National Human Rights Commission encountered operational problems due to the limitation of staffs, and because the proposals of the Commission do not contain legal sanctions. Therefore, it was recommended that the Commission should recruit more human resources complying with work load, formulate a clear operational process in order to reduce time, and to apply persuasion measures to help increase the awareness of relevant government agencies to follow the guidelines proposed by the Commission.